HUMAN RIGHTS AND MIGRATIONS IN THE AMERICAS: REVISITING THE DORZEMA ET AL VS DOMINICAN REPUBLIC CASE - Duhaime, Bernard; Lafontaine, Catherine (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2013)
This article first reviews the principles developed by the Inter-American institutions regarding the human rights of migrants. It also discusses the historical and socio-economic phenomenon of discrimination that prevails in the Dominican Republic against Haitians or Dominicans of Haitian origin, and in which the Case Nadège Dorzema took place. The text then discusses the strategy and legal arguments submitted to the Inter-American Commission and the Court of Human Rights by the victims' representatives to demonstrate how the State violated the former’s right to equality. Finally, the authors analyse the Court's findings on these issues and address the difficulties anticipated regarding the implementation of the judgment.